Breaking the Syntax Barrier: Syntactic Simplification as Avoidance Strategy in L3 Indonesian - Yulianto, Bambang; Margana; Zaim, Muhammad; Asteria, Prima Vidya; Kholiq, Abdul; Katrina Herda, Rozanah; Zakiyah, Muflihatuz (Forum for Linguistic Studies, 2025)
Syntactic avoidance is a recurring yet underexplored phenomenon in third language (L3) acquisition. This study investigates how learners of Indonesian as an additional language simplify or circumvent complex structures in order to sustain communication. Data were collected through semi-structured interviews, oral tasks, and written samples from eight multilingual participants representing six different first language (L1) backgrounds. Thematic analysis identified consistent avoidance patterns, including the omission of subordinate clauses, avoidance of passive voice marked with the di- prefix, simplification of conjunctions, and substitution of relative clauses and modifiers with simpler alternatives. These strategies were found to be shaped by cognitive processing limitations, structural divergence between Indonesian and learners' prior languages, and sociocultural concerns such as politeness and risk of negative evaluation. The study also revealed modality differences, with avoidance more frequent in oral than in written production, suggesting that planning opportunities reduce syntactic simplification. These findings confirm that avoidance is not merely a sign of deficiency but an adaptive interlanguage strategy consistent with cognitive and sociocultural models of multilingual development. Pedagogically, the results highlight the importance of scaffolding complex syntax through sequenced tasks, cross-linguistic awareness, and supportive classroom practices that encourage experimentation. Beyond the classroom, the study underscores the value of understanding avoidance as a dynamic adaptation that reflects multilingual learners' agency in managing communication. The study concludes by recommending future longitudinal and cross-linguistic research to further explore the interplay of cognitive, pragmatic, and sociocultural factors in L3 Indonesian acquisition.